Environmental tobacco smoke exposure and non-syndromic orofacial cleft: Systematic review and meta-analysis - Heba J. Sabbagh; Khlood K. Baghlaf; Hattan M. H. Jamalellail; Abdullah S. Bakhuraybah; Salem M. AlGhamdi; Omar A. Alharbi; Khalid M. AlHarbi; Mona H. A. Hassan (Tobacco Induced Diseases, 2023)
Introduction Environmental tobacco smoke (ETS) is associated with several congenital anomalies, including non-syndromic orofacial clefts (NSOFCs). This systematic review aimed to update the literature on the association between ETS and NSOFCs.